Future Tourism Trends Volume 1 - (:unkn) unknown (Emerald Publishing Limited, 2024)
The future will bring more leisure time, a higher standard of living, and a better quality of life for us all. Future Tourism Trends xamines recent and the most probable changes. The authors present a wide range of visionary insights, as well as operational takeaways.